Antecedents of online purchase intention: a cross-national study between Iran and Malaysia - Eshaghi, S. M. S. (Institute of Electrical and Electronics Engineers Inc., 2016)
This study examines how cultural values influence consumer decision-making with respect to online purchase intention in Iran and Malaysia. The findings suggest that cultural values are antecedents to Website trust, perceived Website privacy and Website quality. As a result, comparing the Iranian and Malaysian models of online purchase intention, Website trust significantly affected the frequency of online shopping in the Malaysian model, but it did not in the Iranian model. The perceived Website privacy and Website quality significantly affected online shopping frequency in the Iranian model, but not in the Malaysian model. The implications of the study were discussed.